2007
DOI: 10.1159/000109406
|View full text |Cite
|
Sign up to set email alerts
|

Association of Met439Thr Substitution in Heat Shock Protein 70 Gene with Postoperative Atrial Fibrillation and Serum HSP70 Protein Levels

Abstract: Background: Atrial fibrillation (AF) is a common arrhythmia encountered following cardiac surgery. Previously, we have shown that higher expression of heat shock protein (HSP) 70 was associated with decreased incidence of postoperative AF (PoAF), suggestive of an antiarrhythmic role. Objective: We have hypothesised that Met493Thr substitution of one of the important hsp70 genes may cause loss of these protective antiarrhythmic effects. We therefore set out to examine the influence of hsp70 genotype on the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 83 publications
1
31
2
Order By: Relevance
“…Recently, a significant association between the C-allele of SNP 3 and increased levels of serum HSP70 has been observed. 39 This interesting finding is consistent with the results of our study, as we observed a protective effect for the C-allele in both populations. Moreover, only two haplotypes, GGC and GAC, contain the C-allele of SNP 3.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recently, a significant association between the C-allele of SNP 3 and increased levels of serum HSP70 has been observed. 39 This interesting finding is consistent with the results of our study, as we observed a protective effect for the C-allele in both populations. Moreover, only two haplotypes, GGC and GAC, contain the C-allele of SNP 3.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, associations have been reported with autoimmune diseases, 40 -43 Parkinson's disease, 44 abacavir hypersensitivity, 45 lung cancer, 46 acute high altitude illness, 47 sarcoidosis 48,49 ischemic stroke 50 and postoperative atrial fibrillation. 39,51 This indicates that HSP70 genes act in many stress-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The selected SNPs are most likely to be markers for variability in production of HSP. These SNPs or others in LD with them correlate with differences in gene expression (Temple et al 2004;Singh et al 2006a, b;Kee et al 2008;He et al 2009) or serum levels (Afzal et al 2008). Although the HSPA1B silent SNP rs1061581 itself does not directly influence HSPA1B mRNA levels (Pociot et al 1993;Schroeder et al 2000), the (A) allele of rs1061581 is in linkage with the major (C) allele of HSPA1B promoter SNP rs6457452 (−179C>T) which is associated with lower levels of HSPA1A/B gene expression (Temple et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The results were supported by findings in a second case-control study. Given the roles played by HSPs in immune surveillance as danger signals (Multhoff et al 1999;Wallin et al 2002;Gehrmann et al 2005) and the known correlations between HSP gene variants and gene expression (Temple et al 2004;Singh et al 2006a, b;He et al 2009) or serum levels (Afzal et al 2008), these results are likely to indicate a primary association and warrant more detailed assessment of the HSP70 genes in childhood ALL development.…”
Section: Discussionmentioning
confidence: 99%
“…The initial rationale for assessing the therapeutic potential of BGP-15 in an animal model with a failing heart and increased susceptibility to AF was related to its role as a co-inducer of the stress inducible form of heat-shock protein 70 (HSP70/72) 12 . Studies in animal models and/or humans suggested that elevated levels of HSP70 (endogenous, genetically manipulated, drug-induced or hyperthermia-induced) were protective against the development of AF, and/or cardiac pathology in settings of ischaemia [13][14][15][16][17][18] . Furthermore, reduced/ defective cardiac HSP70 was associated with an increased risk of postoperative AF in humans 15,16 .…”
mentioning
confidence: 99%